Epithelial Factors Affecting Smooth Muscle Contraction of the Mouse Epididymis - Haas, Dirk Stefan; Justus Liebig University Giessen (My University, 2025)
Urinary tract infections (UTIs) are some of the most common human bacterial infections, ascending up to the kidneys in severe cases. The epididymis, beyond its known functions in sperm maturation, storage, and transport, may also act through its epithelium as a sensory organ capable of detecting pathogens and initiating defensive response, i.e. contraction of its smooth muscles. This study investigates the role of epithelial taste receptor signaling, particularly the Trpm5 ion channel, in mediating smooth muscle contraction in the mouse epididymis. Using immunohistochemistry, a subpopulation of keratin5-positive basal cells with slender processes extending into the lumen was identified. Co-expression with GNAT3, representing the gustatory signaling cascade, and Dclk1, a marker for tuft cells, indicates the presence of the gustatory signaling cascade and the chemosensory nature of these cells, suggesting these cells may detect luminal stimuli, often linked to danger or infection. Time-lapse imaging experiments revealed that application of the bitter compound denatonium benzoate induced a statistically significant increase in contraction frequency in wild type mice, but not in Trpm5 knockout (KO) mice. These findings confirm the involvement of Trpm5-mediated signaling in the contractile response and suggest that epithelial chemosensory cells play a critical role in the defense mechanism of the epididymis. This mechanism may represent a key evolutionary adaptation for protecting ascending UTI.
Keywords: Epithelial Factors Epitidymis; ddc:610